Improvement of Tardive Dyskinesias with Olanzapine - Echater, S.; Oneib, B. (Case Reports in Psychiatry, 2023)
Tardive dyskinesia (TD) is characterized by abnormal and involuntary movements that generally occur after prolonged exposure to neuroleptic medications. In this article, we present the case of a 29-year-old man with schizophrenia who developed TD following treatment with haloperidol. Despite various attempts with benzodiazepines, amantadine, and anticholinergics, the dyskinesias persisted. However, after 2 years of treatment with olanzapine alone, a progressive improvement occurred, leading to the complete disappearance of the dyskinesias. We also provide a brief review of reported cases of antipsychotic-induced TD that has improved with olanzapine.